A influência da afetividade no processo de aprendizagem a partir dos estudos de Chalita nas escolas de Ferreira Gomes - (:unkn) unknown (Brasil, 2022)
The study focuses on the influence of affectivity in the learning process from the studies of Chalita in schools in the municipality of Ferreira Gomes, State of Amapá, specifically in the 3rd year of Elementary education of municipal schools Pastor Jaci Torquato and João Freire Cordeiro. One theme that has been seen by education as a way to obtain good results in school and, consequently, in the adult life of these children. In view of this, it is believed that many problems such as learning difficulties stem from ethical, moral and/or social. It is based on presenting the contributions of the affective relationship to the process of learning, understanding how the affective relationship between teacher and studenthappens within a school context. For this study, in addition to conducting a survey literature there was also a field research of investigative character exploratory, through the application of a questionnaire with objective questions, which contained social, economic and cultural issues. During the child's schooling, it is assumed that there will be several interactions, in which affectivity is present. In this sense, the school must provide a space for reflection on the life of the student as a whole, contributing to the development of a critical conscience and transformative, in which this process should not be dissociated from affectivity, and the teacher is fundamental for the students' learning, making affectivity one of the elements that influence this process. Through the research carried out, it can be seen that affectivity is essential for educational performance, since the words of the children make it very clear that affectivity represents an important aspect in the process of learning, which is based on mutual respect, dialogue and, above all, affection reciprocal.
Keywords: Educação - pedagogia; Atividade escolar - pedagogia; Afetividade - processo de aprendizagem; CNOQ: CIENCIACIAS HUMANAS: EDUCAÇÃO